2016
DOI: 10.1007/s12010-016-2313-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of Mycophenolic Acid by Penicillium brevicompactum Using Solid State Fermentation

Abstract: Solid-state fermentation using the microfungus Penicillium brevicompactum for the production of mycophenolic acid is reported in this paper. Of the initial substrates tested (whole wheat, cracked wheat, long grain Basmati rice, and short grain Parmal rice), Parmal rice proved to be the best. Under initial conditions, using steamed Parmal rice with 80% (w/w) initial moisture content, a maximum mycophenolic acid concentration of 3.4 g/kg substrate was achieved in 12 days of fermentation at 25 °C. The above subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…It has been demonstrated that in some cases the yield of microbial metabolites significantly increased when the strain was subjected to gamma ray -it increased the quantity of obtained mycophenolic acid produced by two strains of Penicillium requeforti [43] in comparison of other cited studies which involved unmodified Penicillium brevicompactum [39,41]. On the other hand, UV radiation was used for the modification of Tolypocladium inflatum which was used for the production of Cyclosporin A [47], however, in the case of that substance there were other studies which resulted in much higher yields [44,45].…”
Section: Modified Strainsmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been demonstrated that in some cases the yield of microbial metabolites significantly increased when the strain was subjected to gamma ray -it increased the quantity of obtained mycophenolic acid produced by two strains of Penicillium requeforti [43] in comparison of other cited studies which involved unmodified Penicillium brevicompactum [39,41]. On the other hand, UV radiation was used for the modification of Tolypocladium inflatum which was used for the production of Cyclosporin A [47], however, in the case of that substance there were other studies which resulted in much higher yields [44,45].…”
Section: Modified Strainsmentioning
confidence: 92%
“…However, in the majority of cases authors added some nutrients to agricultural waste to provide better results of releasing bioactive compounds. In the case of mycophenolic acid produced P. brevicompactum MTCC 8010 from rice bran those supplements were: peptone, KH 2 PO 4 , glycine and methionine [41]. On the other hand, in the case of P. brevicompactum ATCC 16024, the addition of mannitol or (NH 4 ) 2 HPO 4 to pearl barley did not enhance the MA synthesis [39].…”
Section: Optimisation Of Ssf Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…High cell density cultivation of recombinant E. coli cells expressing rhIFN-β protein was done in a laboratory scale bioreactor. The fermentation was carried out in a 3.5 L reactor (Bioflow 3000, NBS with 2-2.5 L working volume) at 37 °C, as described previously (Patel et al 2016;Patil et al 2016). Briefly, in a typical experiment, glycerol stock of recombinant E. coli cells was streaked on a Luria-Bertani (LB)-agar plates containing 50 μg/ml carbenicillin and incubated at 37 °C for ~ 16 h. A single colony of the bacterial cells from the plate was inoculated in 10 ml LB medium, containing 50 μg/ml carbenicillin and incubated overnight at 37 °C (200 rpm).…”
Section: Cultivation Of Recombinant E Coli In a Laboratory Scale Biomentioning
confidence: 99%
“…Mycophenolic acid (MPA) is a secondary metabolite which is mainly produced by fungal species specialy Penicillium brevicompactum (Engel et al, 1982;Schneweis et al, 2000;Puel et al, 2005;Xu and Yang, 2007;Patel et al, 2016Patel et al, , 2017. It has diverse biological properties generally used for the treatment of rejection after organ transplant, psoriasis, and other autoimmune disorders; apart from this MPA also reported as a anticancer agent (Eugui et al, 1991;Zolezzi, 2005;Zheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%